P694 Genetic predisposition and thiopurine-induced pancreatitis in inflammatory bowel disease patients. (25th January 2019) - Burnet, G; de Suray, N; De Vroey, B; Hoang, P; Coche, J-C; Denis, M; Gala, J-L; Dewit, O
Abstract: Background: Thiopurines, Azathioprine and 6-Mercaptopurine, remain an important treatment in both Crohn's disease (CD) and ulcerative colitis but are responsible for several side effects, such as acute pancreatitis (AP) in 3 to 7% of cases. The underlying mechanism of this dose-independent immune-mediated allergic reaction is still unknown. Genetic variability of enzymes intervening in thiopurine metabolism is known to influence adverse events linked to thiopurines. Results for inosine triphosphate pyrophosphatase (ITPA) are controversial. Recent studies on HLA polymorphism demonstrated a significant link between single-nucleotide polymorphism (SNP) rs2647087 and thiopurine-induced pancreatitis (TIP). 1, 2 Methods: Out of 59 patients from five Belgian hospitals with a history of TIP, 42 met the eligibility criteria for AP linked to thiopurine with a positive temporal relationship ( < 4 weeks after thiopurine exposure) and exclusion of other causes of AP. A fully custom PCR amplicon-based target enrichment kit was developed based on the TruSeq Custom amplicon (TSCA) technology from Illumina (Illumina, San Diego, CA, USA). The design of the kit targeted ITPA, HLA-DQA1-HLA-DRB1, but also ABCC4, TPMT, MTHFR and GSTM1, known to intervene in thiopurine metabolism. Results: Our cohort showed high rates of known risk factors for TIP such as CD (88.1%), women (73.8%) and smoking habits (50%). AP were mild or moderate and no early or late complication regarding AP was reported. Hospitalisation rate was 42.9% with a median stay of 6.1 ± 5.43 days. No significant link between ITPA, ABCC4, TPMT, MTHFR, GSTM1 polymorphism and TIP could be found. However, in this cohort, SNP rs2647087 located on HLA-DQA1-HLA-DRB1, was found in high proportions (Allele frequency (AF)=0.476). This AF is similar to Heap et al.'s findings (AF = 0.48–0.49) who demonstrated a significant link between this SNP and TIP (OR = 2.59, p = 2 × 10 −16 ) [1] and slightly lower than Wilson et al.'s results (AF = 0.69) (OR = 15.83, p = 0.0001). 2 Conclusions: TIP is a serious adverse event with important rate and duration of hospitalisation. Prevalence for HLA variant rs2647087 in this TIP cohort is significantly high. Results are similar than in previous studies where heterozygous and homozygous variants experienced a significant increased risk of TIP. Genotyping rs2647087 could be implemented in daily practice when discussing treatment options. Together with TPMT testing, it could be an interesting tool for guiding the physician and the patient in deciding whether or not it is appropriate to initiate thiopurine therapy. No association between ITPA polymorphism and TIP was observed. References 1. Heap GA, Weedon MN, Bewshea CM, et al . HLA-DQA1- HLA-DRB1 variants confer susceptibility to pancreatitis induced by thiopurine immunosuppressants. Nat Genet 2014;46:1131–4. 2. Wilson A, Jansen LE, Rose RV, et al . HLA-DQA1-HLA-DRB1 polymorphism is a major predictor of azathioprine-induced pancreatitis in patients with inflammatory bowel disease. Aliment Pharmacol Ther 2018;47:615–20.